PENGARUH STRES KERJA DAN GAYA KEPEMIMPINAN TERHADAP PRESTASI KERJA KARYAWAN PT. ACTS SURABAYA - Anjar Sulistyowati (J-MACC, 2018)
PT. ACTS surabaya is one of the companies engaged in electronics to manage computer software program. The purpose of this study is to know significantly that affects work stress and leadership style to work performance either partially or together. The results showed that multiple regression analysis can be concluded that there is influence between work stress variable and leadership style on employee work performance of PT. ACTS Surabaya. The overall conclusion of the variable work stress and leadership style together affect the variable work performance of employees of PT. ACTS Surabaya. Based on the t test is known that both independent variables of this study have a significant partial influence on employee work performance of PT. ACTS Surabaya.